An Efficient Green Synthesis of Some Functionalized Spiro Chromene Based Scaffolds as Potential Antitubercular Agents. (18th January 2018) - Khan, Gulzar A.; Naikoo, Gowhar A.; War, Javeed A.; Sheikh, Imtiyaz A.; Pandit, Umar Jan; Khan, Imran; Harit, Amit K.; Das, Ratnesh
Abstract : A facile multicomponent one pot synthesis of novel spiro [chromene‐2, 2‐pyrollidin]‐4 ′ ‐one derivatives3a–l was conveniently carried out in acetic acid at feasible reaction conditions. The reaction mechanism operates through two key intermediates 3‐N‐aryliminocoumarin and coumarinylidene acetone. This protocol is an environmentally benign preparation and gives excellent yields of the target compounds (77–92%). The structure of new compounds were determined by spectroscopic techniques like FTIR, 1 H NMR, 13 C NMR, and MS. Docking studies against enoyl‐acyl carrier protein reductase predicts that the compounds bind at the active site with higher binding affinity values. The compound3k (MIC, 10 μg/mL) shows comparable activity in reference with Isoniazid at the same concentrations against MT H37 Rv. Abstract :